Preferences and opportunities in the marriage market: How comprehensive schooling made the wealthy marry down - Helena Holmlund (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
This paper documents that a shift from a selective to a comprehensive education system had implications for marriage market outcomes. By exploiting an education reform in Sweden, I show that comprehensive education reduced assortative mating both because children from poor backgrounds started to marry up, and because those from wealthy backgrounds became more likely to find a spouse who had grown up in the bottom of the income distribution. The latter result is not explained by higher competition for wealthier partners, nor by increased partnership formation within the immediate peer group which offered more opportunities to meet partners from poorer backgrounds. Instead, the results point to the explanation that comprehensive education exposed the rich to a more diverse set of peers and therefore weakened their taste for homogamy. This finding suggests that familiarity among kids with different backgrounds may affect inter-group closeness and interactions in the long run.
Keywords: I24; I26; J11; 330; assortative mating; homogamy; education reform; peer group